Data Protection Principles, and Customary International Law - Ali, Sanar Shareef (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
Given the rapid technological advancement and cross-border nature of data flows, data protection has become a critical issue of global concern. The absence of a unified, binding global framework has exacerbated the complexity of this issue. Existing legal instruments are either inadequate, non-binding, non-comprehensive, or regional with limited geographical scope. Given the urgent need for international standards in data protection, this article examines the possibility of Customary International Law (CIL) addressing Data protection principles (DPP). The author posits that widespread state practice, combined with existing international and regional legal frameworks, provides a strong basis for the emergence of customary international rules governing DPP.